THE WORLD OF WORK AND TEACHER EDUCATION - FRIEDMANN, Zdeněk (Trends in education, 2013)
The teachers of technical subjects can be of help to pupils with their choice of school/profession. They can inform pupils about the characteristics of different professions, their perspectives, support their interest in handicrafts and make them possible to get at least the partial experience with the profession. The paper is focused on the mentioned aspect of teacher education in the area of career guidance.
Keywords: preparation to career choice; career education; career counseling; education to work; personal skills; teachers of technology; framework curriculum; basic schools